Public transport accessibility tools matter: A case study of Gothenburg, Sweden. Issue 1 (March 2019) - Curtis, Carey; Ellder, Erik; Scheurer, Jan
Highlights: Accessibility tools make a contribution to future urban investment decisions. An accessibility lens gives insight into the latent demand for public transport. An innovative segmentation type approach is employed. A typology provides a framework for a public transport investment strategy. Abstract: Urban transport investment decision-making has relied on traditional modelling tools that forecast travel demand based on existing travel patterns. This approach has also underpinned decisions about future urban development. Latent travel demand is poorly understood, and this is particularly important given policy aspirations for the take-up of more sustainable transport modes such as public transport. Accessibility tools can make an important contribution to future development and investment decisions given this policy aspiration. In this paper, public transport supply is assessed using an accessibility tool and then compared to travel patterns. By assessing both public transport supply and travel demand through an accessibility lens we are able to gain insight into the latent demand for public transport. An innovative segmentation type approach is employed by comparing supply and demand and from this a typology is proposed as a framework for a more holistic public transport investment strategy. This takes into account public transport accessibility, travel demand of trip makers and their socio-economic situation, set in the context of the urban region.